Successful pregnancies in post-kidney transplant couples: four case reports - Huang, Hao; Liu, Xinyu; Lin, Xiaoli; Wu, Xiaoying; Qiu, Yingyin; Huang, Hongfeng (Frontiers in Immunology, 2023)
Background: Female recipients with fertility is increasing with the progression of kidney transplant management. The aim of this article is to evaluate the clinical prognosis of the mothers and the newborns in pregnancies in post-kidney transplant couples. Methods: From January 2019 to April 2022, a total of four couples, all kidney transplant recipients, were successfully prepared for pregnancy after a rigorous preconception evaluation, including three cases of natural conception and one case of in vitro fertilization. Administrations of the mother and newborn, including general clinical condition and laboratory results, were recorded and assessed throughout the pregnancy and till 12 months after delivery. Results: The mean conception age of the mothers was 34.8 years (30-38 years), the mean interval between renal transplantation and pregnancy was 6.6 years (3.7-8.7 years). All deliveries were by cesarean section and alive without incident. Premature births (<37 weeks) occurred in 3 cases (average 35.1 weeks). In case 1 (in vitro fertilization), the maternity experienced pre-eclampsia and the fetal weight was the only case less than 2500g (average 2576.7 g). Mean Apager score (1 min) was 7.8 (6-9) and reached 9 in all cases at 5 minutes. The mothers’ eGFR arose in mid-gestation, decreased in late pregnancy, and largely restored along with proteinuria at 1 year postpartum. Postnatal evaluation at 6 months showed normal neurological development. In addition, the NK cell and IFN-γlevel increased, and the Treg cell and IL-10 level decreased along with preeclampsia occurrence. Conclusions: Pregnancies can possibly succeed in couples who are both kidney transplant recipients. However, higher risks of infertility, prematurity and low birth weight fetuses might still present.